Body image and eating behaviors among university students - Choirunnisa, Rezki Amelia; Harahap, Farida (Psychological Research and Intervention, 2023)
University students are vulnerable to body image and eating behavior problems. This research aims to understand the body image, eating behavior, and the relationship between body image and eating behavior among students at Universitas Negeri Yogyakarta. The research was conducted with 112 students as participants. Body image and eating behavior scales were used as instruments in this study. Pearson's bivariate correlation was employed as the data analysis technique. The results show that students at Universitas Negeri Yogyakarta have a good body image. Moreover, the students' eating behavior is restrained, not too controlled, and not too emotional. There is a relationship between body image and cognitive-restrained eating behavior. A relationship between body image and uncontrolled eating was also found. However, no relationship was found between body image and emotional eating behavior. The contribution of body image to cognitive-restrained eating behavior is 7.4%, while the contribution to uncontrolled eating is 75.6%.